2020
DOI: 10.3390/nano10050948
|View full text |Cite
|
Sign up to set email alerts
|

High Nanodiamond Content-PCL Composite for Tissue Engineering Scaffolds

Abstract: Multifunctional scaffolds are becoming increasingly important in the field of tissue engineering. In this research, a composite material is developed using polycaprolactone (PCL) and detonation nanodiamond (ND) to take advantage of the unique properties of ND and the biodegradability of PCL polymer. Different ND loading concentrations are investigated, and the physicochemical properties of the composites are characterized. ND-PCL composite films show a higher surface roughness and hydrophilicity than PCL alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…NDs (crystal size between 3 and 100 nm) can be purchased commercially as powders or aqueous suspensions. [ 13 ] Typically, ND coatings are processed as part of a composite [ 17,18 ] or via dip coating producing a monolayer‐type thin film. [ 11,19 ] NDs present a cheaper and simpler coating process; albeit with a less compact layer, possible leakage of NDs, and higher variability.…”
Section: Shine Bright: a Closer Look At Diamond‐enhanced Materialsmentioning
confidence: 99%
“…NDs (crystal size between 3 and 100 nm) can be purchased commercially as powders or aqueous suspensions. [ 13 ] Typically, ND coatings are processed as part of a composite [ 17,18 ] or via dip coating producing a monolayer‐type thin film. [ 11,19 ] NDs present a cheaper and simpler coating process; albeit with a less compact layer, possible leakage of NDs, and higher variability.…”
Section: Shine Bright: a Closer Look At Diamond‐enhanced Materialsmentioning
confidence: 99%
“…Tissue scaffolds and surgical implants: Due to the restoring potential for damaged tissue, regenerative medicine, and tissue engineering are of great interest [174][175][176][177]. Like protein-coated materials, ND monolayers have been indicated to act as a suitable platform for the growth of neuronal cells [178].…”
Section: General Applicationsmentioning
confidence: 99%
“…Also, microbial activity decreased with the increase in the ND content. Fox et al [177] also reported the synthesis of PCL/ND composites by the solvent casting method. The results demonstrated that hydrophilicity and surface roughness of the ND-PCL composite films were higher than those of PCL alone.…”
Section: Nanocomposite Scaffolds and Implantsmentioning
confidence: 99%
“…Work by Fox et al showed improved human osteoblast cellular adhesion on their soft composite of polycaprolactone with NDs, when compared to polycaprolactone alone. The ND‐polymer composite was extruded through a needle in a simple design printed prototype scaffold (Fox et al, 2020b). Although this work highlights the potential for additively manufactured diamond composites, it requires improvement to get the mechanical properties and complex geometries closer to those required of implants.…”
Section: Fabrication and Application Of Different Diamond Surfaces Fomentioning
confidence: 99%